Identification of factors which interfere in the conditions of daily living of a community through community diagnoses - Maria do Carmo Andrade Duarte; Maria do Socorro Moura Lins Silva; Marga Simon Coler (Rev Rene)
For the nurse to develop a program or propose an intervention in a community, it is necessary to know those factors that interfere with the achievement and promotion of optimal health in that community and interact with the individuals in thin it. For this reason this quantitative exploratory study were to identify those factors which interfere in the life of the community, identify community nursing diagnoses based on those factors, and propose nursing interventions based on the diagnoses. Data collection was realized in 1996, utilizing structure interviews and systematic observation. The data were analyzed quantitatively, from which two communities nursing diagnoses. Diversion Activity Deficit and Knowledge Deficit of the populace regarding how to obtain resources. Proposed intervention strategies were shared with community leaders. The nurse must be attentive to the importance of implementing the interventions by sharing the responsibility with community in habitants. In this case, communication with community leaders through conscious-raising meeting which would focus on methodology of initiating preventive and therapeutic educational programs and obtaining space and resources activities were proposed.